A mtDNA phylogeny of bustards (family Otididae) based on nucleotide sequences of the cytochromeb-gene - Broders, Olaf; Osborne, Tim; Wink, Michael (Journal für Ornithologie, 2003)
SummaryPhylogenetic relationships of the bustard generaOtis, Ardeotis, Afrotis, Chlamydotis, Eupodotis, Lophotis, andTetrax were inferred from nucleotide sequences of the mitochondrial cytochromeb gene (1143 bp).Otis/Chlamydotis, Ardeotis/Eupodotis meppellii, andLophotis/Tetrax cluster as sibling taxa both in MP and ML reconstructions. The genusEupodotis appears to be polyphyletic. In the genusChlamydotis two distinct groups are apparent,C. u. undulata/C. u. fuertaventurae andC. u. macqueenii. In the case of Cm.macqueenii birds from Sinai show a distinct haplotype. Because of substantial genetic, morphological and behavioural differences, it is suggested attributing species rank toC. undulata undC. macqueenii.
Gesehen am 04.10.2017